Archetype of Male Supernatural Power in Pararaton and Babad Giri Kedhaton - Putut Handoko; Hariyono Hariyono; Kusuma Wijaya (Pioneer: Journal of Language and Literature, 2023)
Abstract: The research deals with the archetype of supernatural power in Pararaton and Babad Giri Kedhaton. How are the supernatural power archetypes portrayed in Pararaton and Babad Giri Kedhaton? The theory of archetype, Pararaton, supernatural power, and a qualitative research design are applied to answer that research problem. The Morphology discussed focuses on the difference between Hindu and Islamic traditions. The finding shows that Pararaton and Babad Giri Kedathon show male-dominated figures. The archetype of male supernatural power in Pararaton and Babad Giri Kedhaton is portrayed as shining, disciplined, and a great achievement as a king. To sum up, the two stories reflect that the heroes (Propp’s idea of a hero) are male holy figures having supernatural power as miracles. Therefore, the fabula of stories has many similarities. However, both books have different traditions so the differences influence how stories are told as the suzhet.